Boron modified TiO2 nanotubes supported Rh-nanoparticle catalysts for highly efficient hydroformylation of styrene. (13th June 2017) - Shi, Yukun; Hu, Xiaojing; Chen, Ling; Lu, Yang; Zhu, Baolin; Zhang, Shoumin; Huang, Weiping
Abstract : Boron modified TiO2 nanotubes supported Rh-nanoparticle is created as a highly efficient catalyst for hydroformylation of styrene. Abstract : The boron modified TiO2 nanotube (B-TNTs) samples were prepared via a hydrothermal treatment and an impregnation method, using boric acid as the boron precursor. Characterization methods including XRD, XPS, SEM and TEM were carried out to elucidate the structural evolution of the samples on the introduction of boron. The samples retained their crystallographic phase as anatase TiO2 after the modification with boron. Rh/B-TNTs catalysts, for the catalytic hydroformylation of styrene, were systematically investigated. It is shown that the boron loading and the B-TNTs preparation method have great effect on the behavior of the catalyst. Experimental results showed that the Rh/B-TNTs-hydrothermal-10% catalyst exhibited the best catalytic performance, affording the highest TOF (up to 18 458 h −1 ). These findings showed that boron modified TNTs can be an important milestone in the search for efficient heterogeneous catalysts for olefins hydroformylation.